Photoluminescence properties of (Al, Ga)N nanostructures grown on Al0.5Ga0.5N (0001). (February 2018) - Matta, Samuel; Brault, Julien; Ngo, Thi-Huong; Damilano, Benjamin; Leroux, Mathieu; Massies, Jean; Gil, Bernard
Abstract: The optical properties of Al0.1 Ga0.9 N nanostructures grown by molecular beam epitaxy on Al0.5 Ga0.5 N (0001) templates are investigated. By combining morphological and photoluminescence (PL) characterizations, we have performed an in-depth analysis of the nanostructures properties as a function of the deposited amount. It is shown that: 1) the nanostructures present an asymmetrical height distribution, and a variation in their shape (i.e. both symmetric and elongated nanostructures are observed); 2) the main PL emission is found in the UV range (above 3.6 eV); and 3) a broad emission in the near UV-blue range is observed. These results allowed to attribute the main PL peak to nanostructures with properties in close agreement to the nominal Al0.1 Ga0.9 N concentration and deposited amount. Concerning the broad PL band at lower energy, it has been correlated to the formation of an additional type of nanostructures with larger size and lower Al composition compared to the Al0.1 Ga0.9 N ones. Highlights: Morphological and optical properties of (Al, Ga)N nanostructures are studied. The ability of Al0.1Ga0.9N QDs to cover the deep UVA range (from 324 to 340 nm). The formation of QDs with different characteristics within the same active layer. The impact of the nanostructure shape on the radiative efficiency.